A percolation network model to predict the electrical property of flexible CNT/PDMS composite films fabricated by spin coating technique. (1st October 2019) - Wu, Di; Wei, Mengni; Li, Rong; Xiao, Tao; Gong, Shen; Xiao, Zhu; Zhu, Zhenghong; Li, Zhou
Abstract: Carbon nanotubes (CNTs) based flexible films have great potential on the flexible electronics due to their relatively uniform electrical properties in the film and ease of fabrication technology. In this work, CNT/polydimethylsiloxane (PDMS) composite films with various film thickness was fabricated successfully. By introducing a percolation network model, this work reveals theoretically that the observed rapidly drops of conductivity in thin films mainly depends on the change of CNT network morphology during spin coating. Junctions formed by structural distorted tubes are also observed at the cross section of film samples. By considering both CNT re-orientation and CNT structural distortion into percolation network model, the simulation results are in good agreement with the experimental data. Furthermore, a comprehensive numerical investigation reveals the relationship between film conductivity and some core parameters including CNT loadings, CNT intrinsic conductivity and CNT aspect ratio. Graphical abstract: Image 1 Highlights: This paper studies the electrical properties of CNT/PDMS composite films of finite size. A new CNT percolation network model is developed by considering both CNT re-orientation and CNT structural distortion. The structural distortion of CNTs is observed expeimently.